Comparative Literature Study: The Role of Women Empowerment in Increasing the Profitability of Umkm in the Era of Society 5.0 - Anisa, Anisa; Lestari, Gunarti Dwi; Yusuf, Ali; Yulianingsih, Wiwin; Mustakim, Mustakim (University of Padjadjaran, 2025)
Women's empowerment plays a crucial role in increasing the profitability of Micro, Small, and Medium Enterprises (UMKM) in the Society 5.0 era, characterized by the integration of digital technology and artificial intelligence. UMKM, as the backbone of the economy, face challenges in remaining competitive in this digital era. Profitability in the context of UMKM refers to a business's ability to generate optimal profits through increased operational efficiency, product innovation, and expanded market share. Women's empowerment in the UMKM sector can make significant contributions through skill enhancement, expanded market access, and product and service innovation that impact business profits. This study aims to analyze the role of women's empowerment in increasing UMKM profitability in the Society 5.0 era. The research method used is a qualitative literature review, with the aim of exploring and interpreting the results of previous studies related to the role of women's empowerment in increasing UMKM profitability in the Society 5.0 era. Data were obtained from books, journals, and articles relevant to the research topic. Based on a review of 10 related journal articles, it was found that women's empowerment not only encourages increased technical and managerial skills but also opens opportunities for access to global resources and markets. However, challenges such as unequal access to technology and funding continue to hamper the potential for women's empowerment. Therefore, policies that support women's empowerment, such as technology-based training and increased access to financing and business networks, are essential to boost UMKM profitability.